Embedding neglected tropical disease programs in national health systems: the Ghanaian experience - Gyapong, Margaret (Henry Stewart Talks, 2019)
Neglected tropical diseases (NTDs), Preventative chemotherapy for NTDs, Progress towards NTD elimination in Africa, Health systems, NTD program implementation in Ghana, Delivery of mass drug administration (MDA) for NTDs, NTD Program health workforce, Health information systems, Control of drugs and supplies, Financing and monitoring and evaluation of the NTD program